Growth differentiation factor-15 as a modulator of bone and muscle metabolism - Hong, Seok Woo; Kang, Jeong-Hyun (Frontiers in Endocrinology, 2022)
This study aims to clarify the potential role of growth differentiation factor-15 (GDF-15) as a myokine in bone metabolism and muscle function in females with osteoporosis. In total, 45 female participants (71.0 ± 8.5 years) with distal radius fractures were recruited. Participants were classified as healthy/osteopenic (n = 28) (CON) or osteoporotic (n = 17) (OP) according to their T-score from the areal bone mineral density (aBMD) of the femoral neck. Body mass index, upper arm and calf circumferences, and handgrip strength were assessed. Total hip, femoral neck, and lumbar spine aBMD was measured via dual-energy x-ray absorptiometry. The focal bone quality of the distal radius was evaluated via 3D reconstructed computed tomographic images. Serum levels of GDF-15, insulin-like growth factor-1, and inflammatory markers such as tumor necrosis factor-α (TNF-α), interleukin-6, and interleukin-1β (IL-1β), as well as the corresponding mRNA levels in the pronator quadratus muscle were determined. Participants in the OP group had higher serum GDF-15 levels than those in the CON group. The mRNA levels of GDF-15, IL-1β, and TNF-α in the pronator quadratus muscle were significantly higher in the OP group than in the CON one. Levels of both serum GDF-15 and GDF-15 mRNA in muscle were positively correlated with age and negatively associated with the aBMD of the total hip and focal bone quality of the distal radius. Handgrip power was not correlated with circulating GDF-15 levels but was correlated with circumferences of the upper arm and calf, and levels of GDF-15 mRNA in muscle specimens. The mRNA levels of GDF-15 were correlated with those of inflammatory cytokines such as TNF-α and IL-1β. The mRNA levels of TNF-α were associated with circumferences of the upper arm and calf and with the aBMD of the total hip. The mRNA levels of GDF-15 in muscle were correlated with serum levels of GDF-15 and TNF-α. GDF-15 may have associations with bone metabolism in humans via paracrinological and endocrinological mechanisms. Maintenance of muscle mass and function would be influenced more by GDF-15 in muscle than by circulating GDF-15. The role of GDF-15 in bone metabolism and muscle homeostasis could be related to inflammatory responses.